Using breast conformation as a body condition scoring system for village chicken - Daud, Hasanah (2016)
This research aim is to evaluate the breast conformation of chicken by using breast conformation as a scoring system for identification of village chicken. This system will set up the body condition score as a method to the body score of chicken. The scoring system will describes the difference body condition for both sex of chicken. It is based on palpating the breast and was developed in both male and female of bird. This scoring method doesn‘t have in village chicken. That‘s why this method should develop to help in compare village chicken with other type of chicken. Akar putra chicken will be used as an indicator to compare with colour broiler chicken. The indicator is use is the indicators used to determine body score of chickens after the cross section of the keel bone is the height of the keel bone thickness of the meat around the keel bone, high size of the keel bone to the spine (frame) and also the size of the ribs. The result show that there was significant difference (P<0.05) for meat around the keel bone and the shape of the breast conformation for the akar putra chicken and colour broiler chicken. The male chicken show that both types of chicken this year showed growing faster rate than female, but female also showed higher meat thickness male chicken. This is because the female takes a long time to grow and eat more than the quantity of food from male to achieve the desired weight. The result show that the color of broiler chicken breast conformation get higher score than akar putra chicken because colour broiler chicken has a faster growth rate than the akar putra chicken. This difference can be seen in weight of 1.5 kg of colour broiler chicken color get score 3 and 4 but the akar putra only get score 2. For the weight 2kg akar putra chicken got a score of 4 chicken and broiler chicken color has reached the score 5. From this research I can conclude that the akar putra can be used to identify the true village chicken because the breast conformation is slim than colour broiler chicken.